Beyond understanding the role of far-field climate in the Gulf of Panama coastal dynamics: an analysis of long-term and seasonal variability of wave systems - Ruby Vallarino-Castillo; José A. A. Antolínez; Vicente Negro-Valdecantos; Jesús Portilla-Yandún (Climate Dynamics, 2026)
Understanding wave systems (WS) dynamics in semi-enclosed tropical basins is challenging due to interactions between remote wave generation and regional climate variability. In the Gulf of Panama, prior studies mainly relied on single-site offshore analyses, limiting characterization of wave energy distribution and its atmospheric and oceanic drivers. This gap in knowledge is particularly consequential for coastal hazard assessments and for deciphering ocean–atmosphere interactions in regions influenced by both long-period swells and low-level wind jets. To address this limitation, we present a comprehensive multi-decadal analysis of the seasonal and long-term variability of significant wave height (Hs) and peak wave period (Tp), based on WS identified applying spectral statistical techniques using the GLOSWAC-5 atlas. To understand the variability and the modulating effect of the Gulf of Panama semi-enclosed morphology, three representative sites at its entrance were selected. Monthly patterns were analyzed by classifying wave trains according to relative orientation (i.e., following, crossing, and opposing) to determine the predominant direction and multimodal activity. Long-term trends were assessed over 17 to 18-year intervals (i.e. 1969–1987, 1988–2005, 2006–2023) using exploratory analysis and quantile regression, with results reported separately for the dry season (December–April) and the wet season (May–November). The analysis revealed five dominant WS, each associated with specific generation mechanisms and geographic origins: WS1, associated with Southern Ocean swells; WS5, originating from Northern Hemisphere swells; WS2, driven by southeasterly trade winds from the subtropical Pacific; and two regionally forced systems, WS3 and WS4, generated by the Panama and Chocó Low-Level Jets, respectively. WS1 shows increases in Hs of about 5–10 cm during 1969–1987 and 1988–2005, and up to ~ 15 cm in 2006–2023, with Tp rising by ~ 0.3–0.6 s over the same intervals. WS2 exhibits small variations, with Hs ranging from − 10 to + 17 cm and Tp fluctuations within ± 0.3 s across the three intervals. WS3 displays the strongest changes, with median Hs increases of 10–30 cm in the first two intervals and extreme values reaching 50–60 cm in 1988–2005 and 2006–2023, together with Tp increments of ~ 0.3–0.5 s. WS4 remains comparatively stable in all periods, with Hs variations within ± 10 cm and Tp changes < 0.4 s. WS5 intensifies mainly in 2006–2023, showing Hs increases of 8–15 cm and Tp rises of ~ 0.2–0.4 s. Monthly mean Hs anomalies (> 0.10 m) at the 50th percentile suggest a relationship with El Niño–Southern Oscillation (ENSO), but analyses using the 95th percentile reveal that only WS2, WS3, and WS4 exhibit a stronger association with ENSO phases.

A Systematic Review of Oceanic-Atmospheric Variations and Coastal Erosion in Continental Latin America: Historical Trends, Future Projections, and Management Challenges - Ruby Vallarino-Castillo; Vicente Negro-Valdecantos; José María del Campo (Journal of Marine Science and Engineering, 2024)
The intricate interplay of oceanic-atmospheric variations has intensified erosive processes on sandy beaches in recent decades, with climate change expected to exacerbate these impacts in the future. Projections for the southern Atlantic and Pacific regions of continental Latin America predict increased extreme events and heightened impacts on sandy beaches, highlighting disparities in studies addressing coastal erosion and its causes. To address these risks, a systematic review is proposed to analyze historical trends and projections, aiming to inform local-level studies and management strategies for at-risk coastal communities. Reviewing 130 research papers, insights reveal the influence of climatic events like El Niño and La Niña on coastal dynamics, as well as the effects of storm intensification and extreme events such as high-intensity waves and storm surges on Latin American coasts, resulting in ecosystem, economic, and infrastructure losses. Projections indicate a rise in the population inhabiting Low Elevation Coastal Zones (LECZ) by the century’s end, emphasizing the urgent need for effective management and planning. Community engagement in erosion monitoring and adaptation programs is crucial for addressing these challenges and developing robust, sustainable, long-term adaptation strategies. This study aims to enhance the understanding of coastal erosion in Latin American communities addressing future coastal risks.

Shoreline Change Analysis Using Historical Multispectral Landsat Images of the Pacific Coast of Panama - Ruby Vallarino Castillo; Vicente Negro Valdecantos; Luis Moreno Blasco (Journal of Marine Science and Engineering, 2022)
The shoreline is the interface between sea and land influenced by natural, anthropogenic factors and climate change. The study of the evolution of the shoreline provides information to evaluate accretion or erosion processes. Shoreline erosion represents a threat to the safety of the coastal population, reducing the extension of the beach zone and making human settlements vulnerable to extreme events. This research presents the analysis of the evolution of the shoreline by multispectral images from Landsat satellites and the Digital Shoreline Analysis System (DSAS) of the Pacific Coast of Panama for the period of 1998–2021. The automated shoreline extraction was generated by combining remote sensing techniques, such as the Histogram Threshold Method and the Band Ratio Method, to generate binary images delineating the land and water zone. The most vulnerable zone, due to erosion processes and the exposition of urban areas, corresponds to the zone of Serena beach and Coronado beach with an average negative distance movement of −23.95 m. Finally, it was concluded that there is a general tendency of erosion processes in the study zone with a rate for long-term analysis of −1.12 m/y (zone I), −1.01 m/y (zone II), and −1.08 m/y (zone III).